The Effect of Premolar Extraction on Tooth Size Discrepancies of the Patients Treated in Orthodontic Department at BSMMU - Anwar, Nabila; Hasan, Gazi Shamim (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
Aims: The present cross sectional study was carried out to investigate the effect of first premolar extraction on tooth size discrepancies (TSD) in an orthodontic population seeking treatment at orthodontic department, BSMMU. Material and methods: Mesiodistal tooth widths were measured on 50 pair of pretreatment and post treatment dental casts of subjects with Class I variation – Class I with bimaxillary proclination, and Class I crowding. The overall ratios and tooth-size discrepancies were determined before and after 1st premolar extractions. Before and after extractions, the subjects were divided into Bolton small (BS), Bolton normal (BN) and Bolton large (BL) overall ratio groups categorized by the Bolton standard deviation definition. Results: The Bolton overall ratio after 1st premolar extraction was smaller than those before extraction in each group. Some of the patients in the BN group and BB group were moved into the BS group and BN group respectively after 1st premolar extraction. A tooth size discrepancy occurred in some patients with normal overall ratios after premolar extractions, but a tooth size discrepancy might be corrected in some patients with big overall ratios after premolar extraction. Conclusion: Orthodontists should take into account the following when devising a treatment plan for premolar extractions, overall ratios might decrease and remain normal, and clinically significant tooth-size discrepancies could change mutually after extractions. Ban J Orthod & Dentofac Orthop, April 2015; Vol-5 (1-2), P.13-16